Comparative analyses of paremias in English, Russian and Uzbek - Sevinch Mirabdullayeva (Genius Journals, 2023)
This article describes the usage of common words in English and Russian (frequently used in everyday life) in paremias, their figurative meanings and Uzbek alternatives and explains the differences.
Keywords: Paremia; literary meaning; figurative meaning; proverb